Q Fever with Unusual Exposure History: A Classic Presentation of a Commonly Misdiagnosed Disease - Randall J. Nett; Earl Book; Alicia D. Anderson (Case Reports in Infectious Diseases)
We describe the case of a man presumptively diagnosed and treated for Rocky Mountain spotted fever following exposure to multiple ticks while riding horses. The laboratory testing of acute and convalescent serum specimens led to laboratory confirmation of acute Q fever as the etiology. This case represents a potential tickborne transmission of Coxiella burnetii and highlights the importance of considering Q fever as a possible diagnosis following tick exposures.